Effect of farmyard manure, elemental sulphur and EDTA on growth and phytoextraction of cadmium by spider plants (Chlorophytum comosum L.) under Cd stress. (February 2023) - Zia-ur-Rehman, Muhammad; Mubsher, Arisha; Rizwan, Muhammad; Usman, Muhammad; Jafir, Muhammad; Umair, Muhammad; Alharby, Hesham F.; Bamagoos, Atif A.; Alshamrani, Rahma; Ali, Shafaqat
Abstract: Cadmium (Cd) contamination is considered as a widespread concern at global scale which is serious threats to human health. Phytoremediation is an eco-friendly approach which can remove or immobilize Cd from the soil. Different organic and inorganic amendments can potentially enhance Cd phytoremediation efficiency but the comparison of farmyard manure (FM), elemental sulphur (S) and ethylenediaminetetraacetic acid (EDTA) for Cd phytoremediation through spider plants ( Chlorophytum comosum L.) remained unanswered. The present study evaluated the efficiency of S (0.1 and 0.2%), EDTA (0.1 and 0.2%, represented as EDTA-0.1 and EDTA-0.2) and FM (0.5 and 1%, represented as FM-0.5 and FM-1) for remediation of Cd contaminated soils (50 and 100 mg kg-1, represented as Cd-50 and Cd-100) through spider plants. Results depicted that the highest shoots and roots dry biomass was found in FM treated plants followed by S, EDTA and control except in EDTA-0.2 treatment in which the lowest values of these parameters were observed. Application of FM-1 significantly increased the shoot dry weight (120%), root dry weight (99%), as well as photosynthetic attributes in Cd-50 as compared to control. Application of EDTA-0.2 increased the bioavailable fraction of Cd than control and the maximum increase was observed in Cd-100. The highest Cd concentrations in shoot and roots were found in EDTA treated plants followed by S, control and FM irrespective of Cd and amendment levels. Maximum Cd in roots (109%) and shoots (156%) was recorded in plants grown in Cd-100 with EDTA-0.2 than control. The maximum bioaccumulation factor, translocation index, harvest index and root to shoot translocation were observed with EDTA than control and other treatments. EDTA along with spider plants may enhance the uptake of Cd but lower biomass production in the highest dose of EDTA may questioned the efficiency of EDTA. Graphical abstract: Image 1 Highlights: Farmyard manure (FM), elemental sulphur (S), EDTA affected the growth and physiology of Cd-stressed C. comosum plants. Biomass of C. comosum was higher with FM than elemental S and EDTA. Use of FM improved the nutrient status of soil than elemental S and EDTA. Higher Cd concentrations in shoots and roots were found with EDTA and elemental S than FM.